Strategies to cut down drinking, alcohol consumption, and usual drinking frequency: Evidence from a British online market research survey. (October 2022) - Sasso, Alessandro; Hernández-Alava, Mónica; Holmes, John; Field, Matt; Angus, Colin; Meier, Petra
Abstract: Background: Relatively little is known about how risky drinkers attempt to moderate their drinking in the absence of specialist support. The broader literature has identified multiple potential strategies that people use to cope with temptation when trying to control health-risk behaviours. This study aims to identify types of alcohol moderation strategies used by British adults, and to explore how concurrent alcohol consumption differs across moderation strategies, focusing on the important role of usual drinking frequency. Methods: We use a continuous repeat cross-sectional survey and one-week drinking diary collected by the market research company Kantar; these provide detailed information on alcohol consumption during a diary week and on how individuals try to moderate alcohol use for 49, 204 British adults trying to reduce their drinking from 2013 to 2019. We use Latent Class Analysis (LCA) to identify predominant types of moderation strategies. With a three-step method, we also analyse the associations between adopting different moderation strategies, measures of frequency and intensity of drinking events, and usual drinking frequency. Results: We found evidence of four alcohol moderation strategies: 29% of individuals use a pre-commitment-focused strategy ( having fewer drinking occasions ), two set of individuals adopt self-control strategies within drinking occasions (specifically 28% select smaller drinks and 5% have fewer drinks ), while 38% adopt a mixed strategy that involves all three. Those using commitment tend to have a higher average consumption per drinking occasion but lower overall weekly consumption compared to those using self-control. Weekly alcohol consumption is particularly high among individuals who are usual everyday drinkers and use self-control to cut down drinking. Conclusion: This analysis provides a useful platform for further work, using prospective or intervention designs, to test the relative effectiveness of different moderation strategies for alcohol consumers who want to reduce their alcohol consumption. Highlights: We investigate types of alcohol moderation strategies in absence of specialist support. We found four moderation strategies based on pre-commitment, self-control, or a mix of the two. The alcohol consumption reported by drinkers differ with the type of strategy adopted. Individuals using self-control strategies report a higher weekly consumption of alcohol. This analysis provides a useful platform for further research on alcohol moderation.